Giant Cell Arteritis Presenting as Ischemic Stroke: A Case Report - Leite, Ana Isabel Bento Ferreira; Mesquita, Gonçalo; Mandim, Andreia; Veiga, Luis; Oliveira, Raquel; Campos, Anita (Brazilian Journal of Case Reports, 2025)
Giant cell arteritis (GCA) is the most common vasculitis over 50 years of age. GCA is an inflammatory condition affecting medium to large sized arteries. GCA is classified into a cranial form (c-GCA) and an extracranial/large vessel form (LV-GCA). Temporal artery doppler ultrasound (TADUS) has become the imaging modality of choice for GCA for rapid diagnosis. Glucocorticoids (GC) remain the primary treatment for GCA. We report the case of a 79-year woman with temporal headache, right hemiparesis and hypoesthesia. She had normocytic normochromic anemia, elevated c reactive protein (CRP) and erythrocyte sedimentation rate (ESR). Brain resonance (BR) revealed bihemispheric infarction. She was diagnosed with left sensorimotor lacunar cerebrovascular accident. TADUS revealed hypoechoic halo in the temporal arteries. c-GCA was newly diagnosed as the aetiology of stroke and treated with GC with resolution of symptoms. Ischaemic stroke is a rare complication in GCA and is a life-threatening condition. This case stands out for the importance of GC as an effective therapy in GCA with symptomatic intracranial involvement, improving their prognosis. In daily practice the early diagnosis of GCA can be challenging.